Autonomous Multisensor Calibration and Closed‐loop Fusion for SLAM. Issue 1 (27th February 2014) - Jacobson, Adam; Chen, Zetao; Milford, Michael; Peynot, Thierry; Monteiro, Sildomar; Kelly, Alonzo; Devy, Michel
<x xml:space="preserve">Abstract</x> The vast majority of current robot mapping and navigation systems require specific well‐characterized sensors that may require human‐supervised calibration and are applicable only in one type of environment. Furthermore, if a sensor degrades in performance, either through damage to itself or changes in environmental conditions, the effect on the mapping system is usually catastrophic. In contrast, the natural world presents robust, reasonably well‐characterized solutions to these problems. Using simple movement behaviors and neural learning mechanisms, rats calibrate their sensors for mapping and navigation in an incredibly diverse range of environments and then go on to adapt to sensor damage and changes in the environment over the course of their lifetimes. In this paper, we introduce similar movement‐based autonomous calibration techniques that calibrate place recognition and self‐motion processes as well as methods for online multisensor weighting and fusion. We present calibration and mapping results from multiple robot platforms and multisensory configurations in an office building, university campus, and forest. With moderate assumptions and almost no prior knowledge of the robot, sensor suite, or environment, the methods enable the bio‐inspired RatSLAM system to generate topologically correct maps in the majority of experiments.